Ibuprofen regulates the expression and function of membrane-associated serine proteases prostasin and matriptase. Issue 1 (December 2015) - Chai, Andreas; Robinson, Andrew; Chai, Karl; Chen, Li-Mei
Abstract Background The glycosylphosphatidylinositol-anchored extracellular membrane serine protease prostasin is expressed in normal bladder urothelial cells. Bladder inflammation reduces prostasin expression and a loss of prostasin expression is associated with epithelial-mesenchymal transition (EMT) in human bladder transitional cell carcinomas. Non-steroidal anti-inflammatory drugs (NSAIDs) decrease the incidence of various cancers including bladder cancer, but the molecular mechanisms underlying the anticancer effect of NSAIDs are not fully understood. Methods The normal human bladder urothelial cell line UROtsa, the normal human trophoblast cell line B6Tert-1, human bladder transitional cell carcinoma cell lines UM-UC-5 and UM-UC-9, and the human breast cancer cell line JIMT-1 were used for the study. Expression changes of the serine proteases prostasin and matriptase, and cyclooxygenases (COX-1 and COX-2) in these cells following ibuprofen treatments were analyzed by means of reverse-transcription/quantitative polymerase chain reaction (RT-qPCR) and immunoblotting. The functional role of the ibuprofen-regulated prostasin in epithelial tight junction formation and maintenance was assessed by measuring the transepithelial electrical resistance (TEER) and epithelial permeability in the B6Tert-1 cells. Prostasin's effects on tight junctions were also evaluated in B6Tert-1 cells over-expressing a recombinant human prostasin, silenced for prostasin expression, or treated with a functionally-blocking prostasin antibody. Matriptase zymogen activation was examined in cells over-expressing prostasin. Results Ibuprofen increased prostasin expression in the UROtsa and the B6Tert-1 cells. Cyclooxygenase-2 (COX-2) expression was up-regulated at both the mRNA and the protein levels in the UROtsa cells by ibuprofen in a dose-dependent manner, but was not a requisite for up-regulating prostasin expression. The ibuprofen-induced prostasin contributed to the formation and maintenance of the epithelial tight junctions in the B6Tert-1 cells. The matriptase zymogen was down-regulated in the UROtsa cells by ibuprofen possibly as a result of the increased prostasin expression because over-expressing prostasin leads to matriptase activation and zymogen down-regulation in the UROtsa, JIMT-1, and B6Tert-1 cells. The expression of prostasin and matriptase was differentially regulated by ibuprofen in the bladder cancer cells. Conclusions Ibuprofen has been suggested for use in treating bladder cancer. Our results bring the epithelial extracellular membrane serine proteases prostasin and matriptase into the potential molecular mechanisms of the anticancer effect of NSAIDs.